Answer:
= 3n + 3
Step-by-step explanation:
The sequence is arithmetic with explicit formula
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
From the recursive formula
a₁ = 6 and d = 3 [ the constant being added to A(n - 1) ] , then
= 6 + 3(n - 1) = 6 + 3n - 3 = 3n + 3
Additive inverses, because their sum is 0
Answer: D
Step-by-step explanation: Im vv sure, is this a test?
1. <span>C) Inverse Property of Multiplication
2. </span><span>B) Inverse Property of Addition
3. </span><span>C) Inverse Property of Multiplication
</span>4. Your answer is not listed (The answer is Associative Property of Multiplication)